THE INFLUENCE OF THE INNOVATIVE EDUCATIONAL ENVIRONMENT IN PRESCHOOL EDUCATION ON THE EDUCATIONAL PROCESS AND THE ACTIVITIES OF PEDAGOGUES - Akramjonova Feruza Akramjonovna, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation: This article describes the important ways of developing the innovative educational environment in the preschool educational organization, the impact on the educational process and the activities of pedagogues. No progress can be achieved without promoting innovation in every branch of the society in accordance with the requirements of the present time. The development of the quality of education through the innovative educational environment is reflected in the reforms carried out in the educational system. Is finding At the same time, the role and importance of the innovative educational environment in the process of education and upbringing in the preschool educational organization was justified through examples. For our country, it is very important to start the  innovative  environment from  preschool  education  organization, which is the lowest level of education, in education and education. An innovative   environment   plays an important role in the organization of a two-way effective  process not only for students, but also for educators. Because the environment  created in the process of education is the main criterion